A Status-Based Multilevel Model of Ethnic Diversity and Work Unit Performance. (February 2017) - Leslie, Lisa M.
The present research builds theory regarding the consequences of work unit ethnic diversity by advancing a status-based, multilevel model of when ethnic diversity is likely to constrain work unit performance. In contrast to past work unit diversity research, which has largely ignored the varying degrees of status ascribed to members of different ethnic groups, I propose that ethnic diversity is most likely to constrain work unit cohesion, and in turn work unit performance, in work units composed of two ethnic subgroups that are separated by large differences in status (i.e., ethnic status subgroups; ESS). Furthermore, and consistent with evidence that the consequences of work unit diversity are contingent on the broader social contexts in which work units are embedded, I predict that the presence of ethnic status subgroups in the community exacerbates the detrimental consequences of ethnic status subgroups in work units. Findings from a multisource, field-based data set ( N = 743 employees nested within 131 bank branches) support the study hypotheses. Implications for theory and practice are discussed.